2006
DOI: 10.1103/physrevlett.96.104302
|View full text |Cite
|
Sign up to set email alerts
|

Self-Propelled Particles with Soft-Core Interactions: Patterns, Stability, and Collapse

Abstract: Understanding collective properties of driven particle systems is significant for naturally occurring aggregates and because the knowledge gained can be used as building blocks for the design of artificial ones. We model self-propelling biological or artificial individuals interacting through pairwise attractive and repulsive forces. For the first time, we are able to predict stability and morphology of organization starting from the shape of the two-body interaction. We present a coherent theory, based on fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
739
1
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 573 publications
(767 citation statements)
references
References 26 publications
21
739
1
6
Order By: Relevance
“…The tendency to match behaviour of nearby neighbours, which is also termed allelomimetic behaviour [53], is typically expressed in an explicit rule of alignment for an individual trying to match the speed and direction of its neighbours. Recent experimental evidence has suggested that it might not be an explicit behavioural rule [41,42], but rather that coordinated motion might be achieved using social repulsion and attraction only (as supported by theoretical models [54][55][56]). Finally, an attraction rule mimics a tendency to group with conspecifics in order to produce aggregation, a prerequisite of school existence.…”
Section: A Typology Of Individual Based Models For Fish Schoolingmentioning
confidence: 94%
“…The tendency to match behaviour of nearby neighbours, which is also termed allelomimetic behaviour [53], is typically expressed in an explicit rule of alignment for an individual trying to match the speed and direction of its neighbours. Recent experimental evidence has suggested that it might not be an explicit behavioural rule [41,42], but rather that coordinated motion might be achieved using social repulsion and attraction only (as supported by theoretical models [54][55][56]). Finally, an attraction rule mimics a tendency to group with conspecifics in order to produce aggregation, a prerequisite of school existence.…”
Section: A Typology Of Individual Based Models For Fish Schoolingmentioning
confidence: 94%
“…Most notably we find that the potential can be classified as one in which the system is "confining" in the large N limit (where N is the number of particles) or non-confining. For second-order systems the language used is H-stability vs. catastrophic to describe the energy per particle in the limit of large N [6,10]. For this paper we are interested in the confining case such that the N → ∞ limit has stable solutions that are confined to some finite region, typically approximating a continuum density (possibly concentrated as a measure).…”
Section: Introductionmentioning
confidence: 99%
“…This has become a widely used tool in the area of complex systems [66,60,69,18,17,32,58]. For example, agent-based models have been used for modeling many types of cooperative behavior [31,56,14,11,24]. In a network context, this approach enables exploration of how changing dynamics of individual agents can affect the evolution of the network, providing control parameters which would be inaccessible in a graph-based model.…”
Section: Agent-based Modelsmentioning
confidence: 99%